Effect of randomized prophylactic nitroglycerin on radial artery spasm during transradial catheterization: An analysis based on operator experience. Issue 3 (14th January 2023) - da Silva, Roberto L.; Dangas, George D.; de Andrade, Pedro B; Joaquim, Rodrigo M.; da Silva, Thais R. W.; Fattah, Tammuz; Pereira, Vanderlei C.; Zanella, Ricardo A.; Sousa, Amanda G. M.; Feres, Fausto; Costa, José R.
Abstract: One limitation to transradial access (TRA) is the occurrence of spasms (RAS), for which the use of prophylactic medications is recommended. Improvement in TRA material combined with the increase in operators' expertise, might mitigate this benefit. We assess the effect of preventive nitroglycerin on RAS during TRA, evaluating the role of the operator's experience. Patients received 500 μg nitroglycerin or placebo. The operator's expertise was classified as: inexperienced (I), intermediate (M), and experienced (E). 2040 patients were included. Prophylactic use of nitroglycerin did not reduce RAS (10.8% vs. 13.4% (placebo), p  = 0.07). RAS incidence was 14.5% in I, 12.5% in M, and 9.7% in E ( p  = 0.01). In group I, nitroglycerin reduced RAS (17.4% vs. 11.1%, p  = 0.04), which was not observed in other groups. Overall, nitroglycerin does not prevent RAS, which is more common among inexperienced operators. More experienced operators could abolish preventive nitroglycerin use.